Prevalence and predictors of anxiety among healthcare workers in Saudi Arabia during the COVID-19 pandemic - Thamer H. Alenazi; Nasser F. BinDhim; Meteb H. Alenazi; Hani Tamim; Reem S. Almagrabi; Sameera M. Aljohani; Mada H Basyouni; Rasha A. Almubark; Nora A. Althumiri; Saleh A. Alqahtani (Elsevier, 2020)
Background: During pandemics, healthcare workers (HCWs) may be prone to higher levels of anxiety than those of the general population. This study aimed to explore the anxiety levels among HCWs in Saudi Arabia during the COVID-19 pandemic and the predictors of increased anxiety levels. Method: HCW participants in this cross-section study were solicited by email from the database of registered practitioners of the Saudi Commission for Health Specialties between 15 May and 18 May 2020. Sociodemographic characteristics, work-related factors, and organization-related factors were collected. Results: Four thousand nine hundred and twenty HCWs (3.4%) responded. Reported levels of anxiety were low anxiety (31.5%; n = 1552), medium (36.1%; n = 1778), and high (32.3%; n = 1590). Participants reporting high anxiety levels were more likely to be unmarried (OR = 1.32, 95% CI: 1.14-1.52); nurses (OR = 1.54, 95% 1.24-1.91); workers in radiology (OR = 1.52, 95% CI: 1.01-2.28); or respiratory therapists (OR = 2.28, 95% CI: 1.14-4.54). Social factors associated with high anxiety levels were: living with a person who is elderly (p = 0.01), has a chronic disease (p < 0.0001), has immune deficiency (p < 0.0001), or has a respiratory disease (p-value <0.0001). Organization-related factors associated with a high level of anxiety were: working in an organization that hosts COVID-19 patients and working with such patients (p-value <0.0001). Conclusion: Self-reported medium and high levels of anxiety were present in 68.5% of HCWs in the COVID-19 pandemic. This highlights the urgent need to identify high-risk individuals to offer psychological support and provide up to date information on the pandemic. These data should help policymakers drive initiatives forward to protect and prepare HCWs psychological wellbeing.